2021
DOI: 10.1177/23315024211003855
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Detention and COVID-19: Pandemic Responses in Four New Jersey Detention Centers

Abstract: On March 24, 2020, a 31-year-old Mexican national in Bergen County Jail, New Jersey, became the first federal immigration detainee to test positive for the novel coronavirus (COVID-19). By April 10, 2020, New Jersey had more confirmed COVID-19 cases among immigration detainees than any other state in the nation. This article examines the relationship between COVID-19 and processes of migrant detention and deportation through a case study of New Jersey — an early epicenter of the pandemic and part of the broade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Our respondents were not confident that either of these practices were happening. Several studies have confirmed their suspicions (Kerwin 2020;Niu and Rhyne 2021;Tosh, Berg, and Leon 2021). Instead, they indicated that DHS moved prisoners around between detention centers, spreading the virus.…”
Section: Continuation Of the Detention And Deportation Machinementioning
confidence: 96%
“…Our respondents were not confident that either of these practices were happening. Several studies have confirmed their suspicions (Kerwin 2020;Niu and Rhyne 2021;Tosh, Berg, and Leon 2021). Instead, they indicated that DHS moved prisoners around between detention centers, spreading the virus.…”
Section: Continuation Of the Detention And Deportation Machinementioning
confidence: 96%
“…They may entrap migrant workers, detainees, and others confined to cramped quarters where the spread of infectious diseases is common. This phenomenon has been present, for example, within US detention centers during the pandemic (see Tosh, Berg and Leon 2021).…”
Section: Ethical Issues In Migration Researchmentioning
confidence: 99%
“…14. Detention numbers fell during the COVID-19 pandemic (Tosh et al 2021). Prior to this, however, the use of detention was trending upward.…”
Section: Implications For Policy and Future Researchmentioning
confidence: 99%
“…The realms of justice and immigration are not exempt from this new (digital) world. While criminal and civil courts, including immigration court, temporarily closed when the pandemic hit, many quickly transitioned to semi-remote or fully remote hearings (Tosh, Berg and León 2021). Postpandemic predictions forecast a new era of digital engagement, hyflex education, and work-from-home models (Castrillon 2020;Lockee 2021).…”
Section: Implications For Policy and Future Researchmentioning
confidence: 99%